DWDM over FSO under the effect of different atmospheric attenuations - Heyam Maraha; Kameran Ali Ameen; Ozlam Abdulhakeem Mahmood; Aras Aldawoodi (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In optical networks, Dense wavelength division multiplexing (DWDM) has been considered as a promising technique to meet the increasing bandwidth demands. It has been used to increase the capacity of long-haul optical transport systems such as free-space optics (FSO) and optical fiber. However, by applying DWDM over the FSO link, different challenges affect the performance system such as clear air, haze and rain atmospheric attenuations. This paper investigates eleven-channel DWDM over FSO based on the electrical linear equalizer that will improve the performance results at the receiver. The channels operate over (1561.42 nm, 1559.79 nm, 1558.17 nm, 1558.55 nm, 1554.94 nm, 1553.33 nm, 1551.72 nm, 1550.12 nm, 1548.51 nm, 1546.92 and 1545.32 nm) wavelengths that have separated based on the traditional International Telecommunication Union (ITU) grid. In the experiments, the system transmits 110 Gbit/s for FSO distances 9500 m, 3000 m, and 2500 m in superbly clear air, haze, and heavy haze atmospheric attenuations, respectively. Over different atmospheric attenuations, we evaluated our system performance using BER, eye diagram and the quality factor (Q-Factor).